2023
DOI: 10.1101/2023.10.16.562038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biological and genomic resources for the cosmopolitan phytoplanktonBathycoccus: Insights into genetic diversity and major structural variations

Louis Dennu,
Martine Devic,
Janaina Rigonato
et al.

Abstract: Population-scale sequencing has become a standard practice to explore the natural genetic diversity underlying adaptation, notably in land plants. However, current sequencing initiatives for eukaryotic phytoplankton primarily concentrate on creating reference genomes for model organisms and characterizing natural communities through metagenomics approaches. Consequently, few species have been thoroughly sequenced and intraspecific genetic diversity remains virtually undescribed, limiting our understanding of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…While barcodes found in the Arctic with non-polar occurrence in global datasets may represent indicators of ongoing species displacement within the Arctic planktonic community, they also stress the limitation of using barcode sequences, such as the variable regions of 18S rRNA, when describing biogeographic patterns of plankton species. The B. prasinos ASV_4580ad6202 was allocated as cosmopolitan and although the genus Bathycoccus is considered cosmopolitan, the analysis of metagenomes (Vaulot et al 2012), of nuclear genomes (Dennu et al 2023; Vannier et al 2016) and of the internal transcribed spacer 2 (Bachy et al 2021) have suggested the existence of distinct Bathycoccus ecotypes and species, including a polar genotype (Dennu et al 2023), all of which have identical 18S rRNA sequences and therefore cannot be discriminated by metabarcodes from the V4 or V9 regions of the 18S rRNA gene. Among diatoms, the polar-temperate ASV_2976201d4c represents at least two distinct Thalassiosira species, T. pacifica and T. aestivalis , which share identical 18S rRNA V4 regions and can be only distinguished by scanning electron microscopy (i.e, T. pacifica was detected by SEM in our samples while T. aestivalis was absent).…”
Section: Discussionmentioning
confidence: 99%
“…While barcodes found in the Arctic with non-polar occurrence in global datasets may represent indicators of ongoing species displacement within the Arctic planktonic community, they also stress the limitation of using barcode sequences, such as the variable regions of 18S rRNA, when describing biogeographic patterns of plankton species. The B. prasinos ASV_4580ad6202 was allocated as cosmopolitan and although the genus Bathycoccus is considered cosmopolitan, the analysis of metagenomes (Vaulot et al 2012), of nuclear genomes (Dennu et al 2023; Vannier et al 2016) and of the internal transcribed spacer 2 (Bachy et al 2021) have suggested the existence of distinct Bathycoccus ecotypes and species, including a polar genotype (Dennu et al 2023), all of which have identical 18S rRNA sequences and therefore cannot be discriminated by metabarcodes from the V4 or V9 regions of the 18S rRNA gene. Among diatoms, the polar-temperate ASV_2976201d4c represents at least two distinct Thalassiosira species, T. pacifica and T. aestivalis , which share identical 18S rRNA V4 regions and can be only distinguished by scanning electron microscopy (i.e, T. pacifica was detected by SEM in our samples while T. aestivalis was absent).…”
Section: Discussionmentioning
confidence: 99%